1989
DOI: 10.1007/bf00052827
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic aerosols and gases in the lower troposphere at Alert Canada in April 1986

Abstract: During April 1986, as part of an international arctic air chemistry study (AGASP-2), ground level observations of aerosol trace elements, oxides of sulphur and nitrogen and particle number size distribution were made at Alert Canada (82.5N, 62.3W).Pollution haze was evident as indicated by daily aerosol number (size > ~.15 mm diameter) an~ SOL = concentrations in the range 125 -260 cm-and ].6 -4.5 ~g m -~, respectively.Haze and associated acidic gases tended to increase throughout the period. SO and peroxyacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 30 publications
4
86
0
1
Order By: Relevance
“…The composition of dust is far more variable than that of sea salt; thus, no single enrichment ratio can be determined for each analyte mass ratio as loaded on to Factor 2. However, the modelled mass ratios of Al to Mg 2+ , K + , V, Cu, As, Se, Sb, and Pb all appear realistic when compared with a variety of crustal sources, with calculated enrichment ratios in the range of 1 to 15 (Taylor, 1964;Barrie et al, 1989;Masson-Delmotte et al, 2013). Specifically, the modelled mass ratio of As / Al (0.00081 m/m) was seen to be closer to that of local soils (0.00013) (Barrie et al, 1989) than the global typical composition (0.00002) (Taylor, 1964;Masson-Delmotte et al, 2013) with enrichment ratios of 6 and 37, respectively (6.3-9.5 and 37-58 25th-75th percentiles per bootstrapping analysis).…”
Section: Factor 2: Crustal Metalsmentioning
confidence: 88%
See 1 more Smart Citation
“…The composition of dust is far more variable than that of sea salt; thus, no single enrichment ratio can be determined for each analyte mass ratio as loaded on to Factor 2. However, the modelled mass ratios of Al to Mg 2+ , K + , V, Cu, As, Se, Sb, and Pb all appear realistic when compared with a variety of crustal sources, with calculated enrichment ratios in the range of 1 to 15 (Taylor, 1964;Barrie et al, 1989;Masson-Delmotte et al, 2013). Specifically, the modelled mass ratio of As / Al (0.00081 m/m) was seen to be closer to that of local soils (0.00013) (Barrie et al, 1989) than the global typical composition (0.00002) (Taylor, 1964;Masson-Delmotte et al, 2013) with enrichment ratios of 6 and 37, respectively (6.3-9.5 and 37-58 25th-75th percentiles per bootstrapping analysis).…”
Section: Factor 2: Crustal Metalsmentioning
confidence: 88%
“…BC is a combustion product from both fossil fuel and biomass burning. While NH + 4 is more commonly associated with agricultural emissions, it can also be produced by biomass burning, vehicle emissions, and some industrial activities (Behera et al, 2013). Most conspicuous in the composition of Factor 3 was the absence of K + , considered to be a tracer of biomass burning which can be a significant source of BC.…”
Section: Factor 3: Black Carbonmentioning
confidence: 99%
“…At higher northern latitudes PAN contributed up to 90% of measured NO W (e.g. Barrie et al, 1989;Solberg et al, 1997) inferring high PAN to NO V ratios. However, these high ratios were normally found during early springtime.…”
Section: No W Budgetmentioning
confidence: 99%
“…Arctic, or middle and upper troposphere). Concurrent observations of PAN and the sum of reactive nitrogen (NO W ) have revealed that PAN can constitute up to 90% of the total NO W budget at higher northern latitudes or higher altitudes (Bottenheim et al, , 1993Barrie et al, 1989;Bottenheim and Gallant, 1989;Muthuramu et al, 1994;Solberg et al, 1997;Sandholm et al, 1992;Singh et al, 1994Singh et al, , 1998Bradshaw et al, 1998;Talbot et al, 1999). Despite lower PAN concentration at lower altitudes in remote marine areas, its decomposition has been found to be su$cient to maintain observed NO V ( "NO#NO ) mixing ratios (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The first and third modes usually exist for desert aerosols (Patterson and Gillette, 1977;Jaenicke and Schiitz,1978), with the first mode being mainly secondary particles, and the third mode soil dust. The second mode, however, is probably an instrumental artifact (Finalayson-Pitts and Pitts, 1986;Barrie et al, 1989), induced by the uncertainty of Mie scattering. Since the scattering complexity in this size range leads to a non-linear response of optical instrument to the particle size.…”
Section: Size Distributions O F Desert Aerosolmentioning
confidence: 99%